Replication of phage phi 29 DNA in vitro: role of the viral protein p6 in initiation and elongation. - Blanco, L (1986)
The phi 29 protein p6 stimulates the formation of the protein p3-dAMP initiation complex when added to a minimal system containing the terminal protein p3, the phi 29 DNA polymerase p2 and phi 29 DNA-protein p3 complex, by decreasing about 5 fold the Km value for dATP. In addition, protein p6 stimulates elongation of the p3-dAMP initiation complex. Whereas the effect of protein p6 on initiation is similar with protein p3-containing fragments from the right or left phi 29 DNA ends, the stimulation of elongation is higher with the right than with the left phi 29 DNA terminal fragment, suggesting DNA sequence specificity. The stimulation by protein p6 of the initiation and elongation steps of phi 29 DNA replication does not require the presence of the parental protein p3 at the phi 29 DNA ends. No effect of protein p6 was obtained on the elongation of the template-primer poly(dT)-(dA) 12-18 by the phi 29 DNA polymerase.